Lipid cubic phase as a membrane mimetic for integral membrane protein enzymes - CAFFREY, MARTIN; LI, DIANFAN (My University, 2011)
The lipidic cubic mesophase has been used to crystallize important membrane proteins for high-resolution structure determination. To date, however, no integral membrane enzymes have yielded to this method, the in meso. For a crystal structure to be meaningful the target protein must be functional. Using the in meso method with a membrane enzyme requires that the protein is active in the mesophase that grows crystals. Because the cubic phase is sticky and viscous and is bicontinuous topologically, quantitatively assessing enzyme activity in meso is a challenge. Here, we describe a procedure for characterizing the catalytic properties of the integral membrane enzyme, diacylglycerol kinase, reconstituted into the bilayer of the lipidic cubic phase. The kinase activity of this elusive crystallographic target was monitored spectrophotometrically using a coupled assay in a high-throughput, 96-well plate format. In meso, the enzyme exhibits classic Michaelis?UOMenten kinetics and works with a range of lipid substrates. The fact that the enzyme and its lipid substrate and product remain confined to the porous mesophase while its water-soluble substrate and product are free to partition into the aqueous bathing solution suggests a general and convenient approach for characterizing membrane enzymes that function with lipids in a membrane-like environment. The distinctive rheology of the cubic phase means that a procedural step to physically separate substrate from product is not needed. Because of its open, bicontinuous nature, the cubic phase offers the added benefit that the protein is accessible for assay from both sides of the membrane.
PUBLISHED
Keywords: Biochemistry; coupled enzyme assay